1983
DOI: 10.1109/tns.1983.4332459
|View full text |Cite
|
Sign up to set email alerts
|

Using Nuclear Resonance Excitation to Observe United Atoms in Symmetric Ion-Atom Collisions

Abstract: SummaryWe consider nuclear resonance excitation as a means to observe the distribution of united-atom orbitals in symmetric ion-atom collisions. We develop this possibility with the application of a two-state adiabatic model to an analysis of a 8Be nuclear resonance experiment. To test our model, and to provide a more direct determination of the nuclear resonance widtn, we propose that the 8Be expeririment be repeated with metastabDle helium targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Feagin and Kocbach [9] based on a molecular orbital model. This model describes evolution of the He + ion plus He ~ atom into Be + states of (ls)22p and 1s(2p) 2 configurations with respective binding energies E** = 386 and 256 eV and equal population probabilities (b~=b~=0.50).…”
Section: Atomic Effects On the C~-c~ Scattering Process The Observedmentioning
confidence: 99%
See 3 more Smart Citations
“…Feagin and Kocbach [9] based on a molecular orbital model. This model describes evolution of the He + ion plus He ~ atom into Be + states of (ls)22p and 1s(2p) 2 configurations with respective binding energies E** = 386 and 256 eV and equal population probabilities (b~=b~=0.50).…”
Section: Atomic Effects On the C~-c~ Scattering Process The Observedmentioning
confidence: 99%
“…We therefore concluded that none of the available models could reproduce the data. Indeed, the Zfirich group [4] as well as Feagin and Kocbach [9] had pointed out that inelastic electron channels also could contribute to the scattering process. In these inelastic channels one or several (up to 3) electrons could be promoted into the continuum.…”
Section: Atomic Effects On the C~-c~ Scattering Process The Observedmentioning
confidence: 99%
See 2 more Smart Citations